INTERNATIONAL EXPECTATIONS AND DOMESTIC PRIORITIES: A THEMATIC ANALYSIS OF UPR RECOMMENDATIONS ADDRESSED TO UZBEKISTAN (Ustozlar uchun, 2026)
This article analyses the thematic recommendations addressed to Uzbekistan during the fourth cycle of the United Nations Universal Periodic Review (UPR). Drawing on the national report submitted by Uzbekistan, the Working Group report, and the thematic list of recommendations compiled by the Office of the High Commissioner for Human Rights, the article examines the principal thematic directions of the recommendations, identifies the rights most frequently addressed, considers the state of implementation and the challenges that remain, and evaluates the role of institutional actors and civil society in the follow-up process. The article further contextualises the recommendations against Uzbekistan's domestic reform agenda and considers their implications for the country's international standing.